Implementasi Manajemen Pendidikan Berbasis Prilaku di MTS Yatashi Kota Bogor - Toyyibudin Toyyibudin (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2022)
In general, the purpose of this study is to reveal the implementation of behavior-based education management at MTs Yatashi, Bogor City. However, the specific objectives of this research are: (1) To determine the implementation of behavior-based education management in MTs Yatashi Bogor City, (2) To determine the implementation of behavior-based education at MTs Yatashi Bogor City. This research is a field research (Field Research) that is conducting research directly to the location to obtain and collect data. The research carried out in the field is examining qualitative problems, namely research data procedures that produce descriptive data in the form of written or spoken words from people and observed behavior. The implementation of behavior-based education management at MTs Yatashi Bogor City is pursued through four alternative strategies in an integrated manner, namely: (a) integrating behavioral education content that has been formulated into all subjects, (b) integrating behavioral education into daily activities at school, (c) integrate behavioral education into programmed or planned activities, (d) build collaborative communication between schools and parents of students. From the discussion above, it can be concluded that the implementation of behavior-based education management is carried out through two activities, namely Intracurricular, namely through teaching and learning activities that have been scheduled by the Deputy Head of curriculum and extracurricular activities, namely scouting, religion, Islamic arts, Youth Red Cross (PMR) which is scheduled by the Deputy Head of the field. to students and the values embedded are religious, disciplined, honest, responsible, tolerance, love the homeland, hard work, care for the environment, love peace, care for social, creative and independent. Keywords: management, education, behavior